If it's not what You are looking for type in the equation solver your own equation and let us solve it.
60=3x-7(-4x+9)
We move all terms to the left:
60-(3x-7(-4x+9))=0
We calculate terms in parentheses: -(3x-7(-4x+9)), so:We get rid of parentheses
3x-7(-4x+9)
We multiply parentheses
3x+28x-63
We add all the numbers together, and all the variables
31x-63
Back to the equation:
-(31x-63)
-31x+63+60=0
We add all the numbers together, and all the variables
-31x+123=0
We move all terms containing x to the left, all other terms to the right
-31x=-123
x=-123/-31
x=3+30/31
| 2|5y-6|-7=5 | | 8j-9j=-j | | 18z-17z=10 | | -36-6r=-36 | | 10=6-x+3 | | 1x+4=0x+5 | | 14=3(x-2)+6 | | n/7+41=34 | | -5(2x-7)=100 | | 18q=19q-10 | | 12x²-18x-12=0 | | 8-3(x-4)=4* | | -29+2x=-(4x-1) | | 3(x+5)-7=32 | | 3(2x+7)=6x+22 | | z+1/9=22+2/9 | | {x}{3}-7=7 | | -12+x+10=-15 | | 1/3x10=1 | | 6x-20=-32 | | -15+v=1+5v | | 10w^2+5w-63=0 | | 3p=-2/4 | | 7=-(x-6) | | x2–2x=0 | | 8x+14+3x−6+x+16=180 | | 4(p+2)=14-2(3-2p)* | | 6.2|-x|=-24* | | 4(p+1)=16 | | n2+8=10 | | n2+ 8=10 | | 2(3x−2)−4x+1=9 |